Toxicity of Organic Fluorophores Used in Molecular Imaging: Literature Review - Raphael Alford; Haley M. Simpson; Josh Duberman; G. Craig Hill; Mikako Ogawa; Celeste Regino; Hisataka Kobayashi; Peter L. Choyke (Molecular Imaging)
Fluorophores are potentially useful for in vivo cancer diagnosis. Using relatively inexpensive and portable equipment, optical imaging with fluorophores permits real-time detection of cancer. However, fluorophores can be toxic and must be investigated before they can be administered safely to patients. A review of published literature on the toxicity of 19 widely used fluorophores was conducted by searching 26 comprehensive biomedical and chemical literature databases and analyzing the retrieved material. These fluorophores included Alexa Fluor 488 and 514, BODIPY FL, BODIPY R6G, Cy 5.5, Cy 7, cypate, fluorescein, indocyanine green, Oregon green, 8-phenyl BODIPY, rhodamine 110, rhodamine 6G, rhodamine X, rhodol, TAMRA, Texas red, and Tokyo green. Information regarding cytotoxicity, tissue toxicity, in vivo toxicity, and mutagenicity was included. Considerable toxicity-related information was available for the Food and Drug Administration (FDA)-approved compounds indocyanine green and fluorescein, but published information on many of the non-FDA-approved fluorophores was limited. The information located was encouraging because the amounts of fluorophore used in molecular imaging probes are typically much lower than the toxic doses described in the literature. Ultimately, the most effective and appropriate probes for use in patients will be determined by their fluorescent characteristics and the safety of the conjugates.